Research on a New type of Wiper Assembly Based on New Energy Vehicle Electrical System. Issue 5 (April 2021) - Deng, Qingjun; Li, Peipei; Zhao, Yi; Liu, Yong; Hu, Jianyu; Song, Shijie
Abstract: This paper analyzes the research status of commonly used wiper assembly. It propos es a wiper assembly which is applied to new energy vehicles. Moreover, a new set of wiper ass embly device is developed and the hardware design and software programming of the device h as been accomplished. This device is used to test the cleanliness and noise of the front windshi eld of a car. And the test results are presented. The test shows that the device has stable perfor mance, simple operation and it meets the cleaning requirements of new energy vehicles. This p aper provides technical support and technical reference for the research and development work of new energy vehicles and electronic parts enterprises.